1991
DOI: 10.1111/j.1744-6570.1991.tb00696.x
|View full text |Cite
|
Sign up to set email alerts
|

Personality Measures as Predictors of Job Performance: A Meta‐analytic Review

Abstract: The purpose of this study was to investigate conflicting findings in previous research on personality and job performance. Meta‐analysis was used to (a) assess the overall validity of personality measures as predictors of job performance, (b) investigate the moderating effects of several study characteristics on personality scale validity, and (c) appraise the predictability of job performance as a function of eight distinct categories of personality content, including the “Big Five” personality factors. Based… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

31
600
3
25

Year Published

1995
1995
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 1,135 publications
(678 citation statements)
references
References 79 publications
31
600
3
25
Order By: Relevance
“…These results are fairly consistent with results found in North American metaanalyses (Barrick & Mount, 1991;Hough, Eaten, Dunnette, Kamp, & McCloy, 1990;Hurtz & Donovan, 2000;Tett, Jackson, & Rothstein, 1991). It is also important to note that the Big Five personality characteristics have been replicated in an impressive series of studies, across raters and rating scales, but also in different countries and cultures (Collins & Gleaves, 1998;Ghorpade, Hattrup, & Lackritz, 1999;Saucier, Hampson, & Goldberg, 2000).…”
Section: Does the Criterion-related Validity Of Selection Proceduressupporting
confidence: 78%
“…These results are fairly consistent with results found in North American metaanalyses (Barrick & Mount, 1991;Hough, Eaten, Dunnette, Kamp, & McCloy, 1990;Hurtz & Donovan, 2000;Tett, Jackson, & Rothstein, 1991). It is also important to note that the Big Five personality characteristics have been replicated in an impressive series of studies, across raters and rating scales, but also in different countries and cultures (Collins & Gleaves, 1998;Ghorpade, Hattrup, & Lackritz, 1999;Saucier, Hampson, & Goldberg, 2000).…”
Section: Does the Criterion-related Validity Of Selection Proceduressupporting
confidence: 78%
“…Neuroticism means a tendency to be worried, touchy, nervous and strenuous. Previous research shows that neuroticism is associated with low job performance (Tett et al 1991), including low earnings (Gelissen and de Graaf 2006;Judge et al 1999;Sutin et al 2009), as well as low job satisfaction (Judge et al 2002). Hence, there is no surprise that it also predicts disability retirement.…”
Section: Discussionmentioning
confidence: 99%
“…In empirical research, neuroticism appears to be the most consistent predictor of job success amongst the Big Five personality traits. Tett et al (1991) found that, in a meta-analysis, neuroticism was adversely correlated with job performance. Later research has confirmed this finding; for example, individuals high in neuroticism have significantly lower earnings (Gelissen and de Graaf 2006;Judge et al 1999;Sutin et al 2009).…”
Section: Personality and Workmentioning
confidence: 99%
“…Our research suggests that gene flow helps to explain why a large variety of individual personality differences are preserved in large populations with many different social and ecological environments available. The various alleles, which produce personality differences, seem to be very efficient at preserving themselves (Dawkins, 1977), since individuals with different personality traits actively search for a suitable environment (Barrick & Mount, 1991;Hettema & Kenrick, 1992;Scarr & McCartney, 1983;Tett, Jackson, & Rothstein, 1991). This explains why alleles influencing these personality traits are eliminated with difficulty through natural selection, thus preserving high population variability.…”
Section: Discussionmentioning
confidence: 99%